Nitric oxide modulates angiotensin II-induced endothelial vasoconstrictor prostanoid release - Jerez, Susana Josefina (2005)
This study investigated the modulation of angiotensin II-induced endothelial prostanoid release in rabbit aortic rings. Two cumulative dose response curves with 90-min washing interval were performed. Incubation with l-NG-nitroarginine methyl ester (l-NAME) 10- 4 M increased angiotensin II maximal contractile response (Emax). This effect was reversed by indomethacin 10- 5 M, diphenyliodinum 10- 5 M, Tempol 10- 5 M or ascorbic acid 10- 4 M in both cumulative dose response curves and by SQ 29548 10- 6 M in the second cumulative dose response curve. When segments were treated with tetraethylamonium 10- 3 M but not with glibenclamide 10- 5 M during the washing period, l-NAME recovered its ability to enhance the E max in arteries incubated with SQ 29548. Conclusions: nitric oxide modulates angiotensin II-induced endothelial release of cyclooxygenase-dependent eicosanoids, one of which acts through thromboxane A2/prostaglandin H2 receptors and would decrease KCa channel activity. An increase in free radical production may account for the enhancement of such prostanoid release. Furthermore, it was found that in the present conditions, the release of the hyperpolarizing factor would improve in order to maintain the vascular tone.